Ei, broto, vamos ao cinema?: o Cine-teatro Irapuã e a sociabilidade em Itororó-BA nas décadas de 60 e 70 - Santos, Clédson Luciano Miranda dos (2009)
This work aimed to reflect on the broader dynamics and importance that the cinema was to sociability in Itororó city, Bahia, in the 60 s and 70 s of the Twentieth Century. It s more specific focus fell on the Cine-teatro Irapuã that, among the many movies-goers in the city, stood out in the imagination and memory of those who attended, or worked in the cinema. The reports and interviews with former residents of the Itororó society, opened itself to the importance of recovery of memory on film and cultural practices, particularly focusing on sociability and identity of its residents. Based, mainly in studies of the reception and critical analysis on the cultural industry, the thesis addresses questions about the relationship between cinema, art, culture and the entertainment industry. It also draws a discussion on the public relations mimetic down from the images conveyed in the film. The history of Brazilian cinema, from its inception until the 70's, served as backdrop to the debate on the peak and the disappearance of movie theater in Itororó, opening up for some considerations on a possible resumption through new experiences in the reflexive potential of cinema